A German view on the Baltic Sea region - Claus-Friedrich Laaser; Klaus Schrader (Baltic Rim Economies, 2018)
For Germany and the other large BSR neighbors Poland an the Russian Federation Baltic Sea trade is of minor importance. The BSR is only one integration area — i.e. destination of its exports and origin of its imports — among a lot of peers being located in other directions of the compass rose. Moreover the BSR in a narrower sense is characterized by a high degree of economic heterogeneity — a North-South downward gradient of wealth can be observed. This wealth gap at the Baltic Sea implies diverging economic interests.
Keywords: F15; F02; 330; Ostseeraum; Wirtschaftsintegration